Holonic recursiveness with multi-agent system technologies - Suarez, Sonia (2014)
Recursive Systems are often needed or recommended for automatically deploy or build a software system composed of multiple entities on a large network, or on distributed locations, without a central control. We use the recursive definitions proposed in holonic systems, as the recursiveness is an elemental structural property of their structure. Holonic systems are used to be implemented using MAS technologies (platforms) on the basis of the shared functional properties of autonomy and cooperation of agents and holons. This paper discusses the adequacy of the actual MAS technologies for holonic recursiveness implementation. A comparison of MAS platforms is done through a framework that will guide the decisions of designers and developers.